Relationship between Fiber Fineness and Diameter of Three Bast Fibers - Qian Geng; Chengfeng Zhou; Kai Nie; Wanwan Lv; Haoxi Ben; Guangting Han; Wei Jiang (Journal of Natural Fibers, 2022)
Natural plant fibers are outstanding materials in textile industry. The fiber fineness, length and strength are three of the most important indexes to evaluate the fiber quality. Fiber fineness refers to the thickness of the fiber, which is usually expressed by the mass per unit length. The relationship between fiber fineness and fiber diameter is very important for deeper understanding of a new fiber. In this study, three different natural fibers were collected to measure the fiber fineness, diameter, and density. Furthermore, SEM was conducted to detect the fiber cross section, and the correlation equations were constructed between the fiber fineness and diameter. Results showed that vibration method could generate a lower fiber fineness value; all the correlation equations had high accuracy to predict fiber fineness with different diameters, and most of the prediction errors were lower than 10%. In the final equations, the coefficients were 0.825, 0.69, 0.975 of apocynum, ramie, and kenaf fiber, respectively.